Social Media and the Public’s Involvement in the Disaster’s Narrative (Case Study: Bantul Regency, Indonesia) - Sukarno, Mohamad; Qodir, Zuly (The Journal of Society and Media, 2023)
This research aims to discuss the disaster narration during the PPKM period on the Bantul Regency’s social media. This research uses the qualitative method from interviews and social media data analyzed by the Computer Assisted Qualitative Data Analysis (CAQDS). The data were showcased in crosstab analysis and word cloud analysis. The result shows that 1 Bantul District has succeeded in building a community understanding of crises rather than increasing the reputation of actors. The narrative built through crisis knowledge created by the Regional Disaster Relief Agency (BPBD) Bantul Data and Information Center (Pusdalops) needs to be better informed. 2) Then, in the social media dimension of Twitter, COVID-19 data is only presented with updates without showing collaboration between actors. 3) public interaction on BPBD Bantul’s Twitter social media was primarily positive, with 63% (supporting all parties in tackling COVID-19), damaging 21% (distrust in COVID-19 data), and neutral 11% (impartial). In word cloud analysis, the dominance of words often used as narratives is Bantul with 31 counts, followed by data, COVID-19, district PPKM, etc.